Advanced Studies in Contemporary Mathematics 26 (2016), No. 4, pp. 607–625 - MESSIRDI, BEKKAI; AZZOUZ, ABDELHALIM; DJELLOULI, CHOUTI (My University, 2016)
The relations of similarity, quasi-similarity, almost similarity, asymptotic similarity and compalence are discussed in this paper. Various spectral results on these notions are presented. In addition, we establish the link between invariant subspaces and hyperinvariant subspaces with quasi-similarity, almost similarity and compalence operator properties.